Pengaruh Kompensasi, Motivasi dan Pengembangan Karier terhadap Kinerja Pegawai Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kabupaten Pinrang - Nuhardi, Rudi; Akhmad, Akhmad; Harrang, Agussalim (Universitas Batanghari Jambi, 2025)
This study explores the impact of compensation, motivation, and career development on the performance of employees at the Human Resources Development and Personnel Agency of Pinrang Regency. Employing a quantitative approach, the research engaged all 39 employees as both the population and sample. Data were gathered through questionnaires and analyzed using multiple linear regression. The findings reveal that compensation exerts a positive yet insignificant influence on employee performance. Similarly, motivation demonstrates a positive but statistically insignificant effect. In contrast, career development significantly and positively affects employee performance, underscoring its pivotal role in driving productivity.